2022
DOI: 10.1002/jia2.26028
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the incidence and burden of HIV by age among women who sell sex: a systematic review and meta‐analysis

Abstract: Introduction:Young women who sell sex (YWSS) are at heightened risk of HIV acquisition and transmission and are among the least engaged in HIV services. There is insufficient epidemiologic evidence characterizing the burden of HIV among YWSS, particularly as compared to older WSS. These data are needed to design and tailor effective HIV prevention and treatment programmes for this population. Methods: We conducted two parallel systematic reviews and meta-analyses to define both the immediate and long-term HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“… 98 Data from South Africa suggest that sex work dynamics are changing, with the mean age of sex workers and durations at-risk both increasing, 99 while young women who engage in sex work remain at highest incidence risk. 100 Different sampling and recruitment approaches are also likely to have identified different women for study inclusion. Studies have shown that participants recruited through respondent-driven sampling are younger than those recruited through venue-based snowball sampling.…”
Section: Discussionmentioning
confidence: 99%
“… 98 Data from South Africa suggest that sex work dynamics are changing, with the mean age of sex workers and durations at-risk both increasing, 99 while young women who engage in sex work remain at highest incidence risk. 100 Different sampling and recruitment approaches are also likely to have identified different women for study inclusion. Studies have shown that participants recruited through respondent-driven sampling are younger than those recruited through venue-based snowball sampling.…”
Section: Discussionmentioning
confidence: 99%
“…33 Preliminary findings from South Africa suggest that sex work dynamics are changing with the mean age of sex workers increasing and longer durations at-risk, 34 whilst young WESW remain at highest incidence risk. 35 Different sampling and recruitment approaches were also likely to identify different women for study inclusion. Studies have shown that participants recruited through RDS are younger than those recruited through venue-based snowball sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Data were insufficient to estimate pooled age-disaggregated IRRs which may have provided further insights, given evidence of higher incidence among younger WESW. 35 For all but one study which provided a comparator non-WESW group, 24 our IRR denominators were based on extrapolations of subnational estimates backwards in time parallel to national female incidence trajectories. Whilst this approach aimed to capture spatial variation over time, there is substantial uncertainty in these subnational incidence denominators, particularly for older studies, which is not reflected in the calculated IRRs.…”
Section: Discussionmentioning
confidence: 99%
“…was 24 years (IQR 20-28). Almost one-fifth (17.5%) of FSWs reported that they first began sex work before the age of 18 years, with the median age of sex work initiation in this group being 16 years (IQR 15-17), and the median age at which they were regularly selling sex being 18 years (IQR [16][17][18][19][20][21][22][23].…”
Section: Sociodemographic and Participant Characteristicsmentioning
confidence: 99%
“…These adverse outcomes are often accompanied by stigma and discrimination, violence from official authorities, and barriers to healthcare 19. While some studies report an increased prevalence of HIV in adolescent girls and young women (AGYW) who initiate sex work under the age of 18 years compared with those who initiate sex work as adults,12 20 21 others find no significant difference in HIV prevalence between the two groups 9 10 21…”
Section: Introductionmentioning
confidence: 99%